Developing a new model to control risk and improve quality in the construction industry by integrating risk management and quality function deployment - Abdulrahman, Al Tekreeti Ahmed Muneer; Haron, Nuzul Azam; Ales, Aidi Hizami; Hua, Law Teik (International University of Sarajevo, 2024)
The construction industry is considered an indicator of a country's development through buildings, residential complexes, investment projects, roads, bridges, and infrastructure projects. Dynamic and complex features characterise this industry, which is directly and significantly affected by external and internal factors, in addition to the influences of its stakeholders. These characteristics and factors are considered one of the main reasons for generating risks in this industry, which can affect the quality and reputation of the construction project if its Risk Management systems are not followed systematically and correctly. Poor quality of construction projects has become a visible and widespread feature worldwide, including in Malaysia. Risk management is still applied on a low level in many projects within the construction industry. Quality Function Deployment is considered an essential modern system that focuses on quality, customer needs, and satisfaction, which can serve the construction industry if linked with risk management tools. The study's primary purpose is to find the relationship between RM and the QFD and develop a modern model for risk control in the construction industry through their integration. The conceptual framework of the proposed model is developed and applied to stakeholders in the construction industry in Malaysia. The results confirmed a solid, complementary, and interconnected relationship between RM and QFD, which can develop a new model for controlling risks and thus improve the construction project's quality. The results of the study recommended adopting this model. Recommendations were made to researchers to develop the model in the future to include broader areas in the construction industry.